Stress level and body composition among gender / Noor Fatihah Ilias, Nur Syafiqah Khanum Mohamed Fuad and Nur Iman Zahira Muhamad Zamani - Ilias, Noor Fatihah; Mohamed Fuad, Nur Syafiqah Khanum; Muhamad Zamani, Nur Iman Zahira (Universiti Teknologi MARA, 2021)
Academic stress is the emotional or mental state that students experience during their university life as they pursue their studies. Stress is known as a major factor that contributes to weight gain. The purpose of this study is to identify the relationship between stress level and body composition (BMI) of FSR Sports Science male and female undergraduate students. This is the causal-comparative study which involves female and male students of SR243 from the Faculty of Sport Science and Recreation, UiTM Shah Alam. The sample analysed was N = 291 consist of 148 female students and 143 male students. This study used PSS-14 questionnaire distributed among the sample to collect demographic details and body composition measured by BMI calculation data. The findings reported that there is no significant difference, p = > 0.05 between genders (male and female) on stress level but shows a significant difference, p = < 0.05 on Body Mass Index (BMI). Findings described a weak positive relationship between stress level and BMI among gender for female r = 0.102, and for the male is r=0.029. A weak positive correlation between stress level and body composition, r = 0.049. BMI has significant difference with female and male SR243 undergraduates' students and has no significant difference among gender on stress level. A weak positive linear relationship was found between stress level and body composition among gender in Faculty of Sports Science and Recreation.